Daniel Achondo S. A. business case: the crossroads of growth - Oliva, Ismael (Estudios de Administración, 2011)
At the beginning of March 2010, the general manager of Daniel Achondo S. A., together with its executive committee, was preparing the first board of directors of the year. The group had experienced a gradual process of growth since its creation in 1961, becoming a benchmark company in the Chilean automotive market. However, Daniel Achondo S. A., whose development was under a closed and family corporate governance, faced new and important strategic challenges regarding how it should grow. it was well positioned, along with the Volkswagen brand, in its target segment; it had improved the organizational structure and consolidated a collegiate corporate governance; but for CEO Daniel Achondo Faz the question of diversification persisted. Among the options he was considering at the time were: continue to grow exclusively with the Volkswagen brand, or take the distribution of another car brand